Tamano de parcela - Voysest Voysest, Oswaldo (United Nations Development Programme, 1985)
The factors influencing the size and shape of exptl. field plots (area of exptl. lot, soil types, trial objective, no. of replicates, and degree of accuracy and homogeneity of the exptl. material) for the execution of field expt. are discussed. The basic principles of the following different methods to determine plot size are described: max. curve method, method of Koch and Rigney, Hatheway's method, and the max. curve method using the multiple linear regression model. Some considerations are presented on the border effect and on plot size in bush and climbing bean trials. (CIAT)